2013
DOI: 10.4319/lo.2013.58.5.1531
|View full text |Cite
|
Sign up to set email alerts
|

Two spatial scales in a bleaching event: Corals from the mildest and the most extreme thermal environments escape mortality

Abstract: In summer 2010, a bleaching event decimated the abundant reef flat coral Stylophora pistillata in some areas of the central Red Sea, where a series of coral reefs 100-300 m wide by several kilometers long extends from the coastline to about 20 km offshore. Mortality of corals along the exposed and protected sides of inner (inshore) and mid and outer (offshore) reefs and in situ and satellite sea surface temperatures (SSTs) revealed that the variability in the mortality event corresponded to two spatial scales … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 40 publications
3
69
0
Order By: Relevance
“…The large diurnal tidal range in the Kimberley region (8-12 m) causes fairly expansive intertidal habitat subject to highly variable water temperatures, ranging up to *7°C over a single diel cycle. This makes the nearshore intertidal of Cygnet Bay comparable to other high and variable temperature environments where scleractinian coral is abundantly found, such as backreef habitats in American Samoa (Craig et al 2001;Oliver and Palumbi 2009) and outer reef environments of the Red Sea, albeit not quite as extreme as in the Persian Gulf (Riegl et al 2011;Bauman et al 2013) or nearshore environments of the Red Sea (Pineda et al 2013). Furthermore, the temperature of coral tissue within the shallower and more isolated pools in Cygnet Bay (B0.2 m deep) could be reaching in situ temperatures of up to *36°C at midday in summer due to the stagnant water motion being limited to flows on the order of *1 cm s -1 or less at low tide (Fabricius 2006;Jimenez et al 2008).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The large diurnal tidal range in the Kimberley region (8-12 m) causes fairly expansive intertidal habitat subject to highly variable water temperatures, ranging up to *7°C over a single diel cycle. This makes the nearshore intertidal of Cygnet Bay comparable to other high and variable temperature environments where scleractinian coral is abundantly found, such as backreef habitats in American Samoa (Craig et al 2001;Oliver and Palumbi 2009) and outer reef environments of the Red Sea, albeit not quite as extreme as in the Persian Gulf (Riegl et al 2011;Bauman et al 2013) or nearshore environments of the Red Sea (Pineda et al 2013). Furthermore, the temperature of coral tissue within the shallower and more isolated pools in Cygnet Bay (B0.2 m deep) could be reaching in situ temperatures of up to *36°C at midday in summer due to the stagnant water motion being limited to flows on the order of *1 cm s -1 or less at low tide (Fabricius 2006;Jimenez et al 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, these reef communities also support reasonable levels of coral cover (25-26 %) and high diversity (Craig et al 2001) with reasonably robust rates of coral growth (*1.4 g cm 2 yr -1 ; Smith et al 2007). In the Red Sea, Pineda et al (2013) found higher rates of bleaching in corals living on the more exposed, seaward sides of nearshore reefs than corals living on the more protected, shoreward sides, despite much higher temperature elevations and variations within the more protected sites, thus suggesting some form of environmentally dependent resilience related to prior history of thermal variability and exposure (Carilli et al 2012;Castillo et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Applying these bleaching thresholds to predictions of regional ocean temperatures from coupled ocean-atmosphere global circulation models has given us the means to predict the frequency of future bleaching events under different climate scenarios on regional and global scales (Teneva et al 2011;Frieler et al 2012;van Hooidonk et al 2013). A number of studies have shown, however, that the in situ temperatures of nearshore waters at the local or reef scale (, 1 km) can deviate significantly from the temperature of offshore waters (Leichter et al 2006;Castillo and Lima 2010;Pineda et al 2013). Furthermore, spatial variations in water temperature and bleaching intensity within nearshore reef systems can occur over tens to hundreds of meters (Davis et al 2011;van Woesik et al 2012;Pineda et al 2013).…”
mentioning
confidence: 99%
“…A number of studies have shown, however, that the in situ temperatures of nearshore waters at the local or reef scale (, 1 km) can deviate significantly from the temperature of offshore waters (Leichter et al 2006;Castillo and Lima 2010;Pineda et al 2013). Furthermore, spatial variations in water temperature and bleaching intensity within nearshore reef systems can occur over tens to hundreds of meters (Davis et al 2011;van Woesik et al 2012;Pineda et al 2013). Such small-scale variations in temperature and thermal stress could thus pose a challenge for predicting the bleaching or reduced growth of corals based solely on offshore sea surface temperatures (SST; McClanahan et al 2007;Maynard et al 2008;Weeks et al 2008).…”
mentioning
confidence: 99%
“…In general, low temperature stress increases with depth (Bak et al, 2005;Bongaerts et al, 2015) and were not harmful in the study area [i.e., lowest recorded daily mean temperature from 2005 to 2013 at the shelf edge Grammanik Bank Tiger mesophotic reef site ( Figure 1C) was 25.1 • C at 38 m depth, Smith et al, 2013]. High temperature stress causing coral bleaching has been shown to impact the seaward edge of shallow (<5 m) fringing reefs more severely in the Red Sea, possibly because of lowered thermal tolerance in the moderated mean thermal climate, relative to inshore reefs, caused by the nearby connection to cooler oceanic water (Pineda et al, 2013). The southeastern Puerto Rican shelf within a few kilometers of the shelf edge is sufficiently deep to allow relatively free exchange with oceanic water; during the annual thermal maximum (September to November) mean daily temperatures decrease only slightly (∼0.2 • C) going inshore at similar depths.…”
Section: Chronic Processes As a Control On Mesophotic Habitat Structurementioning
confidence: 99%